2018
DOI: 10.1111/ter.12330
|View full text |Cite
|
Sign up to set email alerts
|

A 70 Ma record of suprasolidus conditions in the large, hot, long‐duration Grenville Orogen

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Similar tectonic scenarios have been presented elsewhere (Billerot, Duchêne, Vanderhaeghe, & de Sigoyer, ; Duchêne, Aïssa, & Vanderhaeghe, ), and have been explained as a result of extrusion of the core of the orogen which ultimately lead to an increase in temperature (Goscombe et al., ). These high‐temperature events may last several tens of million years (Duchêne et al., ; Turlin et al., ; Vanderhaeghe, ), and are best explained by lithospheric break‐off during collision (Goscombe et al., ) and not by slab break‐off after subduction (Meneghini et al., ) especially when the geological evidence for subduction is weak or absent. It has been argued that such high‐ P /low to medium‐ T conditions are more representative for the whole orogenic belt and that later high‐ T /medium ‐P conditions together with partial melting and intrusion of granitic melts in structurally higher levels results from collapse of the orogenic core followed by heat advection from the underlying mantle (Vanderhaeghe, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar tectonic scenarios have been presented elsewhere (Billerot, Duchêne, Vanderhaeghe, & de Sigoyer, ; Duchêne, Aïssa, & Vanderhaeghe, ), and have been explained as a result of extrusion of the core of the orogen which ultimately lead to an increase in temperature (Goscombe et al., ). These high‐temperature events may last several tens of million years (Duchêne et al., ; Turlin et al., ; Vanderhaeghe, ), and are best explained by lithospheric break‐off during collision (Goscombe et al., ) and not by slab break‐off after subduction (Meneghini et al., ) especially when the geological evidence for subduction is weak or absent. It has been argued that such high‐ P /low to medium‐ T conditions are more representative for the whole orogenic belt and that later high‐ T /medium ‐P conditions together with partial melting and intrusion of granitic melts in structurally higher levels results from collapse of the orogenic core followed by heat advection from the underlying mantle (Vanderhaeghe, , ).…”
Section: Discussionmentioning
confidence: 99%
“…980-950 Ma) are marked by the thermal relaxation of the continental crust following gravitational spreading and weakening of the convergence that led to orogenic collapse and thinning of the crust associated with low cooling rates of ca. 2-6°C/Ma (Turlin et al, 2018). This is witnessed in the medium to low pressure crustal segment of the Allochthonous Belt (aM-LP, Fig.…”
Section: The Crevier Alkaline Intrusion In the Late-grenvillian Tectomentioning
confidence: 89%
“…1b) by the apatite diffusion modeling that yielded a closure temperature of apatite crystals of 550-450°C at ca. 960 Ma (Turlin et al, 2018). Two mechanisms have been proposed to account for this http://www.petrology.oupjournals.org/ thermal evolution, a slab retreat (Turlin et al, 2018) or a lithospheric foundering (also referred to delamination; Corrigan & Hanmer, 1997;Groulier et al, 2018b) of the subcontinental lithospheric mantle.…”
Section: The Crevier Alkaline Intrusion In the Late-grenvillian Tectomentioning
confidence: 99%
See 1 more Smart Citation
“…and references therein). Due to its capability to incorporate 238 U during crystallization, apatite is amenable to U-Pb dating, which has been successfully used to date hydrothermal and magmatic events (e.g., Corfu and Stone, 1998), or thermal overprints in metamorphic terranes (e.g., Bruguier et al, 2002;Flowers et al, 2006;Kirkland et al, 2017Kirkland et al, , 2018Hall et al, 2018;Turlin et al, 2018). Recent studies have also demonstrated its potential for sedimentary provenance studies (Chew et al, 2011).…”
Section: Introductionmentioning
confidence: 99%